IMPROVING AON HEWITT INDONESIA EMPLOYEE ENGAGEMENT SURVEY PRODUCT USING ENGAGEMENT-JOB BURNOUT MODEL - Adyansyah Patonangi; Aurik Gustomo (Jurnal Manajemen Indonesia, 2018)
Aon Hewitt Indonesia (AHI) as global HR consulting firm serves in Indonesia providing employee engagement survey for their clients. The survey is to assess the company's employee engagement condition and with key deliverables solutions to improve the employee engagement condition. Recently some AHI clients have expressed their dissatisfaction concerning the employee engagement model that AHI used on their survey product, as it is too focus on what client needs to provide for its employees and there is no assessment of what makes the employee become disengaged. A new employee engagement model using the complete twodimensional observations through the engagement-job burnout condition is developed as the alternative solution to overcome the deficiencies which come from AHI's survey product using the old model. From the employee engagement survey using the new model it provides several outputs to help client improve the engagement and prevent job burnout on their employees as follows; the current client's engagement and job burnout score, statistical analyses on the key area of work life to be improved corresponding to improve engagement and prevent job burnout, and the suggestion regarding actionable solutions for client to implement in space of one year after the survey has finished. Keywords—Aon Hewitt Indonesia employee engagement survey, Engagement, Job burnout, Key areas of work life, Statistical analysis. Abstrak Aon Hewitt Indonesia (AHI) sebagai perusahaan konsultansi HR dunia yang beroperasi di Indonesia menyediakan survei keterikatan pegawai kepada klien-kliennya. Survei ini untuk menilai kondisi keterikatan pegawai pada suatu perusahaan dan dengan keluaran kunci solusi-solusi untuk meningkatkan kondisi keterikatan pegawai. Belakangan ini beberapa klien dari AHI menunjukkan ketidakpuasan terhadap model keterikatan pegawai yang digunakan AHI. Masukan-masukan dari klien mengatakan bahwa model yang digunakan terlalu fokus terhadap apa yang dibutuhkan oleh klien untuk diberikan kepada pegawai-pegawainya, dan tidak adanya penilaian terhadap apa yang membuat pegawai menjadi tidak terikat. Model baru untuk keterikatan pegawai menggunakan observasi dua dimensi yang lengkap melalui kondisi keterikatan-kelelahan kerja dikembangkan sebagai solusi alternatif untuk menutupi kekurangan-kekurangan yang ada pada model lama. Dari survei keterikatan pegawai menggunakan model yang baru, memberikan beberapa keluaran untuk membantu klien dalam meningkatkan keterikatan pegawai terhadap perusahaan dan menghindarkan pegawai untuk merasa lelah dalam bekerja sebagai berikut: nilai keterikatan pegawai dan kelelahan bekerja pegawai terkini, analisa statistik terhadap area utama kehidupan kerja untuk meningkatkan keterikatan pegawai dan menghindarkan pegawai untuk merasa lelah dalam bekerja, dan saran mengenai solusi yang dapat ditindaklanjuti untuk diimplementasikan oleh klien dalam jangka waktu satu tahun setelah dilaksanakannya survei. Kata kunci—Survei keterikatan pegawai Aon Hewitt Indonesia, Keterikatan, Kelelahan kerja, Area utama kehidupan kerja, Analisis statistik.